Meningkatkan Kemampuan Menulis Teks Deskripsi Melalui Minat Membaca (Studi Pada Siswa Kelas V MI Arrohmah Bekasi) - Hasanah, Ropiatul; Samosir, Astuti; Permana, Adi (Jurnal Pendidikan Impola, 2025)
This study aims to analyze the effect of reading interest on the descriptive writing skills of fifth-grade students at MI Arrohmah Bekasi. The background of this research stems from the low writing skills of students, which are largely influenced by their lack of interest in reading. Reading plays an essential role in enriching vocabulary, broadening knowledge, and enhancing students’ imagination. With a higher interest in reading, students are expected to compose descriptive texts more comprehensively, clearly, and engagingly. This research employed a quantitative approach with a quasi-experimental design, specifically the Post-Test Only Control Group Design type. The population comprised all fifth-grade students of MI Arrohmah Bekasi totaling 110 students, and the sample consisted of 44 students selected through simple random sampling. The research instruments included a reading interest questionnaire and a descriptive writing skills test. The data analysis results revealed a positive and significant effect of reading interest on students’ descriptive writing skills. The hypothesis test using the t-test produced a t-value of 3.79, which is greater than the t-table value of 2.009 at a 0.05 significance level. These findings indicate that increasing reading interest contributes to improving students’ descriptive writing ability. This study recommends that teachers integrate reading literacy programs into Indonesian language learning as a strategy to enhance students’ writing skills.